Incarcerated paraesophageal hernia and gastric volvulus: Management options for the acute care surgeon, an Eastern Association for the Surgery of Trauma master class video presentation. Issue 6 (June 2020) - Coleman, Conley; Musgrove, Kelsey; Bardes, James; Dhamija, Ankit; Buenaventura, Percival; Abbas, Ghulam; Wilson, Alison; Grabo, Daniel
Abstract : Supplemental digital content is available in the text.